Empathy and the Schwartz Value System: A Test of an Integrated Hypothesis - BALLIET, Daniel Patrick (Institutional Knowledge at Singapore Management University, 2008)
This study examined the relationship between Schwartz's (1992) 10 universal values and individual differences in empathy (Davis, 1983). Trait empathy was predicted to have the strongest positive relationship with benevolence values and the strongest negative relationship with achievement values. The pattern of correlations between empathy and the 10 values was closely associated with the predicted rank order of the correlations based on the Schwartz value system, but also varied slightly between a non-religious university (n = 284)and a religious university (n = 179).